2016
DOI: 10.1124/jpet.116.233296
|View full text |Cite
|
Sign up to set email alerts
|

New Insight into the Dietary Cause of Atherosclerosis: Implications for Pharmacology

Abstract: At present, the guideline approach to the medical treatment and prevention of atherosclerotic cardiovascular disease (ASCVD) is to classify patients by risk and treat the known risk factors (contributory causes), e.g., hypertension, diabetes, obesity, smoking, and poor diet, as appropriate. All high-risk patients should receive statins. This approach has had substantial success but ASCVD still remains the number one cause of death in the United States. Until recently, the underlying cause of ASCVD remained unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…Convincing evidence suggests an association between TMAO and inflammation with increased TNF-a, and IL-6 [ 44 ]. As we observed, the high level of TMAO in the PTB < 7 d group, with significant predictive value and correlated with GAB and CL, which might be the consumption of a choline or L-carnitine-containing diet during pregnancy [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 88%
“…Convincing evidence suggests an association between TMAO and inflammation with increased TNF-a, and IL-6 [ 44 ]. As we observed, the high level of TMAO in the PTB < 7 d group, with significant predictive value and correlated with GAB and CL, which might be the consumption of a choline or L-carnitine-containing diet during pregnancy [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 88%
“…Other studies propose the use of DMB, an analogue of choline that inhibits choline TMA lyase. DMB can be found in some foods like balsamic vinegars, red wines or extra-virgin olive oil and grapeseed oil [ 96 ]. Although it inhibits the transformation of choline, carnitine and crotonobetaine into TMA in mice and rats, DMB is not able to avoid the complete TMAO synthesis as it cannot inhibit the conversion of GBB to TMA [ 8 , 17 , 32 , 38 ].…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…TMAO has been described as a toxic substance, and it has been suggested that broad-spectrum inhibitors of the bacterial TMA-lyase enzymes that generate TMA – the precursor of TMAO – may ‘revolutionize the preventive treatment’ of atherosclerotic cardiovascular disease [5]. The idea of enriching animal feeds with TMAO to improve their performance and growth [6] is, however, not in accordance with the assumption that TMAO is toxic.…”
mentioning
confidence: 99%
“…Optimism has been expressed regarding the prospect of using TMA-lyase inhibitors as new pharmaceutical drugs against cardiovascular disease [5]. The concept is to reduce TMAO production in the liver by inhibiting the production of precursor TMA in the gut.…”
mentioning
confidence: 99%